Clinicoepidemiology of Skin Diseases in Children Seen at the University Hospital Center Morafeno, Toamasina, Madagascar - Irina Mamisoa Ranaivo; Fandresena Arilala Sendrasoa; Malalaniaina Andrianarison; Moril Sata; Onivola Raharolahy; Dimby Stephane Ralandison; Lala Soavina Ramarozatovo; Fahafahantsoa Rapelanoro Rabenja (Hindawi Limited, 2021)
Introduction. The child's skin diseases are common and very diverse. Many studies concerning pediatric dermatoses have been carried out in Africa and the rest of the world. Few epidemioclinical data reflect these skin diseases in children, especially in the east coast of Madagascar. We aim to describe the pattern skin diseases among children seen at the University Hospital Center Morafeno, Toamasina, Madagascar. Patients and Methods. A retrospective study over a 3-year period from January 2017 to December 2019 was conducted in children seen in the Dermatology Department of University Hospital Center Morafeno, Toamasina, with skin diseases. Results. During the study period, 347 children out of the 1584 new patients were retained with a sex ratio of 0.86. The mean age was 6.4 years old. The main diseases identified were skin infectious diseases (43, 23%), allergic dermatoses (24.21%), and autonomous dermatosis (15.56%). Conclusion. Our study revealed the importance of infectious and allergic dermatoses in Toamasina. It is necessary to carry out simple preventive actions such as hygiene.